THE INFLUENCE OF ORGANIZATIONAL CULTURE AND PERCEIVED ORGANIZATIONAL SUPPORT ON EMPLOYEE ENGAGEMENT WITH ORGANIZATIONAL COMMITMENT AS A MEDIATOR - Hanna Amanda; Pantius Drahen Soeling (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
The focus of this research is how to improve employee engagement at the PT.X head office by examining the relationship between organizational culture and organizational perceptions of employee engagement with organizational commitment as a mediator. This research uses quantitative approach, which is a study that aims to explain a cause of the occurrence of social phenomena, which the phenomenon will be explained by conducting an objective measurement. Primary data collection through the dissemination of questionnaires to 74 respondents. Data analysis using the partial least square equation model or can be known as SEM-PLS. Based on the results of research that has been found, it can be concluded that organizational culture variable does not give a significant direct positive influence on employee engagement, whereas when viewed on variables perceived organizational support and organizational commitment, these two variables have a significant positive direct affect on employee engagement. If the direct influence relationship between organizational culture and employee engagement does not have a significant influence, but when the variable is mediated by organizational commitment, then the results state that there is a significant positive influence relationship between the two variables. This shows that the organization's commitment to succeed has a significant role in mediating the relationship between organizational culture and employee engagement.